Fundamentals of invertebrate palaeontology : macrofossils - Jain, Sreepat (Springer geology., 2017)
This book provides practical morphological information, together with detailed illustrations and concise texts explaining each entry. The book details the morphological characters of each organism, providing fundamental information for palaeontologists and palaeobiologists alike. Each chapter starts with a brief introduction and goes on to describe the organism's morphology in detail, followed by a brief note on classification and lastly illustrated examples of stratigraphically important organisms through time along with their major distinguishing characters. The book includes over 3000 clearly labelled, hand-drawn and classroom-friendly illustrations of over 1200 species.